URGENSI PENGESAHAN RUU PERAMPASAN ASET DALAM PEMULIHAN KERUGIAN NEGARA AKIBAT KORUPSI: PERSPEKTIF YUDIRIS NORMATIF - Pardede, Rudi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Corruption in Indonesia has caused state losses of up to trillions of rupiah annually, while existing legal mechanisms still focus on criminalizing perpetrators and are not optimal in recovering state assets. The disparity between state losses and recovered assets (state loss recovery gap) highlights the weakness of regulations that rely solely on confiscation of assets through criminal decisions (conviction-based asset forfeiture). This study uses a normative juridical method with a legislative, conceptual, and comparative approach to examine the urgency of ratifying the Asset Forfeiture Bill. The results of the study indicate that the implementation of the Non-Conviction Based Asset Forfeiture (NCB) mechanism is highly relevant to addressing obstacles to law enforcement, particularly in cases where perpetrators have fled, died, or are difficult to prove criminally. Internationally, similar mechanisms have been implemented effectively in the United States, the United Kingdom, and Switzerland, and are in accordance with the mandate of the 2003 United Nations Convention against Corruption (UNCAC). However, the ratification of this bill remains hampered by political resistance and concerns about abuse of authority. Therefore, transparent, accountable regulatory design and oversight by an independent judiciary are necessary to ensure this legal instrument functions optimally. In conclusion, the ratification of the Asset Confiscation Bill is a strategic step to strengthen corruption eradication, close the state loss recovery gap, and restore public rights more equitably. Keyword: corruption, asset forfeiture, Non-Conviction Based Asset Forfeiture, UNCAC, asset recovery Abstrak: Korupsi di Indonesia telah menimbulkan kerugian negara hingga triliunan rupiah setiap tahun, sementara mekanisme hukum yang ada masih berfokus pada pemidanaan pelaku dan belum optimal dalam memulihkan aset negara. Ketimpangan antara kerugian negara dan aset yang berhasil dikembalikan (state loss recovery gap) memperlihatkan kelemahan regulasi yang hanya mengandalkan perampasan aset melalui putusan pidana (conviction-based asset forfeiture). Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan komparatif untuk mengkaji urgensi pengesahan Rancangan Undang-Undang (RUU) Perampasan Aset. Hasil kajian menunjukkan bahwa penerapan mekanisme Non-Conviction Based Asset Forfeiture (NCB) sangat relevan untuk mengatasi hambatan penegakan hukum, terutama pada kasus pelaku yang melarikan diri, meninggal dunia, atau sulit dibuktikan secara pidana. Secara internasional, mekanisme serupa telah diterapkan efektif di Amerika Serikat, Inggris, dan Swiss, serta sesuai dengan amanat United Nations Convention against Corruption (UNCAC) 2003. Namun, pengesahan RUU ini masih terkendala resistensi politik dan kekhawatiran penyalahgunaan kewenangan. Oleh karena itu, diperlukan desain regulasi yang transparan, akuntabel, serta diawasi peradilan independen agar instrumen hukum ini dapat berfungsi optimal. Kesimpulannya, pengesahan RUU Perampasan Aset merupakan langkah strategis untuk memperkuat pemberantasan korupsi, menutup celah state loss recovery gap, dan memulihkan hak-hak publik secara lebih adil. Kata kunci: korupsi, perampasan aset, Non-Conviction Based Asset Forfeiture, UNCAC, pemulihan aset.